Single-Switch High Step-Up Zeta Converter Based on Coat Circuit - Binxin Zhu (IEEE, 2021)
By the negative influence of parasitic parameters from the components, the voltage step-up capacity of basic dc-dc converters is limited at extremely high duty cycle. Which makes the traditional dc-dc converters are difficult to be applied to renewable energy generation systems such as fuel cell and photovoltaic (PV) systems. In this study, a single-switch high step-up Zeta converter is proposed based on the basic Zeta converter and corresponding coat circuit. By using the coat circuit, the proposed converter not only can achieve higher voltage gain, but also acquire lower voltage stress on the semiconductor devices. Therefore, the devices with lower conduction resistances can be used to improve the efficiency. Furthermore, the coat circuit is composed of passive components, which does not change the continuous output current characteristic of the basic Zeta converter. And the proposed converter has only one active switch, the drive and control circuits are simple. The operation principle and the performance analysis of the proposed Zeta converter are described in detail, and a 300 W closed-loop experimental prototype has been developed for verification.